Analisis dan Perancangan Sistem Informasi Eksekutif Dashboard Data E-Government berbasis Service pada Pemerintah Kabupaten Sidoarjo - Rivalno Al Fath Ismubandono; Widhy Hayuhardhika Nugraha Putra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Government of Sidoarjo Regency especially the Communication and Information Office (Diskominfo) has the task to connect the Organisasi Perangkat Daerah (OPD) to present the government data from each OPD. During this time, the presentation and delivery of government data to the Mayor of Sidoarjo Regency still uses manual process that requires a lot of time and effort because Diskominfo must process data sent by the OPD in the form of Excel worksheet into diagrams and graphs so that the Mayor can easily understand the data from OPD. Data sent by OPD is still not in the form information packages, so data processing takes a long time. This will take a long time for the Mayor to make decisions. Based on this problem, the Executive Information System Dashboard E-Government needed is needed based on Android and Website so when Mayor need government's data can be accessed either through mobile or computer applications by taking data from the data warehouse. Analysis and design of this sistem will use object-oriented design analysis (OOAD) method. From the results of this study, current business processes and proposals are generated, user needs, system design and user interface. The results of the design of this system are evaluated by traceability matrix and consistency analysis. The results of the design evaluation show that user needs have been defined and facilitated and have a high level of consistency and can help the Mayor in viewing government data contained in the Executive Information System Dashboard E-Government.